A dynamic niche provides Kit ligand in a stage-specific manner to the earliest thymocyte progenitors - Buono, M; Giustacchini, A; Mead, A; Jacobsen, S; Nerlov, C; Facchini, R; Matsuoka, S; Thongjuea, S; Luis, T; Besmer, P (Nature Publishing Group, 2015)
Thymic T-cell development is initiated from bone marrow-derived multi-potent thymus seeding progenitors (TSPs). During the early stages of thymocyte differentiation progenitors become T-cell restricted. However, the cellular environments supporting these critical initial stages of T-cell development within the thymic cortex are not known. We here use the dependence of early, c-Kit–expressing thymic progenitors on Kit ligand (KitL) to show that CD4–CD8–c-Kit+CD25– DN1-stage progenitors associate with, and depend on the membrane-bound form of KitL (mKitL) provided by, a cortex-specific KitL-expressing vascular endothelial cell (VEC) population. In contrast, the subsequent CD4–CD8–c-Kit+CD25+ DN2 stage progenitors associate selectively with cortical thymic epithelial cells (cTECs) and depend on cTEC-presented mKitL. These results show that the dynamic process of early thymic progenitor differentiation is paralleled by migration-dependent changes to the supporting niche, and identify VECs as a thymic niche cell, with mKitL as a critical ligand.